2016
DOI: 10.1007/s11356-016-7562-8
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in indigenous microbial communities during the anaerobic degradation of pentachlorophenol in upland and paddy soils from southern China

Abstract: Pentachlorophenol (PCP) is a common persistent pesticide in soil that has generated a significant environmental problem worldwide. Therefore, anaerobic degradation of PCP by the soil indigenous microbial community has gained increasing attention. However, little information is available concerning the functional microorganisms and the potential shifts in the microbial community associated with PCP degradation. In this study, we conducted a set of experiments to determine which components of the indigenous micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The application of a pesticide can effectively prevent disastrous losses of grain yield and promote economic growth in the agricultural industry, but its degradation is affected by many factors, including soil type, pH, organic matter content and soil microbial communities. We speculate that there is consistency in the effects of fomesafen [7,8]. Previous authors have reported a residual half-life of fomesafen of 133 days when used in a soybean field of anthrosols in Hangzhou, and of 14.2 days when used in a soybean field of anthrosols in Chuzhou [9].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The application of a pesticide can effectively prevent disastrous losses of grain yield and promote economic growth in the agricultural industry, but its degradation is affected by many factors, including soil type, pH, organic matter content and soil microbial communities. We speculate that there is consistency in the effects of fomesafen [7,8]. Previous authors have reported a residual half-life of fomesafen of 133 days when used in a soybean field of anthrosols in Hangzhou, and of 14.2 days when used in a soybean field of anthrosols in Chuzhou [9].…”
Section: Introductionmentioning
confidence: 74%
“…The pH was determined via the potassium chloride leaching solution method. The organic matter content was determined via the potassium dichromate heating oxidation method [7]. The whole nitrogen used was potassium borate with copper sulfate as the selenium powder, and the automatic analyzer used was determined by nitrogen analysis.…”
Section: Soilmentioning
confidence: 99%